Cryptanalysis of an Enhanced Spatiotemporal Chaotic Image/Video Cryptosystem. (15th March 2011) - Yoon Yoon, Eun-Jun Eun-Jun; Hong Hong, Jeong-Woo Jeong-Woo; Yoon Yoon, Sang-Yoon Sang-Yoon; Park Park, Dong-In Dong-In; Choi Choi, Myung-Jin Myung-Jin
Abstract : Recently, an enhanced spatiotemporal chaotic image/video cryptosystem was proposed by Rhouma and Belghith. This paper demonstrates that the enhanced cryptosystem is not secure against the following three different classical types of attacks: chosen plaintext, chosen ciphertext, and known plaintext. In the three attacks, only a pair of (plaintext/ciphertext) was needed to totally break the cryptosystem.